2008
DOI: 10.1002/jmv.21083
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a new, fully automated immunoassay for detection of HTLV‐I and HTLV‐II antibodies

Abstract: Screening blood donations for human T-lymphotropic virus types I and II (HTLV-I/II) continues to be important in protecting the safety of blood products and controlling the global spread of these retroviruses. We have developed a fully automated, third generation chemiluminescent immunoassay, ARCHITECT rHTLV-I/II, for detection of antibodies to HTLV-I/II. The assay utilizes recombinant proteins and synthetic peptides and is configured in a double antigen sandwich assay format. Specificity of the assay was 99.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 47 publications
2
11
0
1
Order By: Relevance
“…The situation regarding HTLV-1 in Nicaragua and Costa Rica is poorly known but rare studies revealed similar relatively low HTLV-1 prevalence rates (0.2–0.7%), among the Nicaraguan and Costa Rican adult populations (Khabbaz et al, 1990; Qiu et al, 2008). In Belize, Guatemala and El Salvador, no HTLV-1 record about the prevalence of the HTLV-1 infection has been published to our knowledge.…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%
“…The situation regarding HTLV-1 in Nicaragua and Costa Rica is poorly known but rare studies revealed similar relatively low HTLV-1 prevalence rates (0.2–0.7%), among the Nicaraguan and Costa Rican adult populations (Khabbaz et al, 1990; Qiu et al, 2008). In Belize, Guatemala and El Salvador, no HTLV-1 record about the prevalence of the HTLV-1 infection has been published to our knowledge.…”
Section: Htlv-1 Worldwide Distribution and Prevalence Estimates By Gementioning
confidence: 99%
“…A variety of serological screening kits are available, including chemiluminescent enzyme immunoassays (CLEIAs), chemiluminescent immunoassays, and particle agglutination assays, followed by confirmation by Western blotting (WB) (5)(6)(7)(8)(9). WB measures the serological reaction to both Gag core proteins (p19, p24, and p53) and the Env protein gp46 (10).…”
mentioning
confidence: 99%
“…CLIA (Qiu et al, 2008), and ECLIA (Laperche et al, 2017). These assays are available in Japan because they are capable of processing large numbers of samples in a relatively short time.…”
Section: Assays For Htlv-1 Antibody Screeningmentioning
confidence: 99%